2010
DOI: 10.1377/hlthaff.2010.0314
|View full text |Cite
|
Sign up to set email alerts
|

Health Reform In Massachusetts Cut The Uninsurance Rate Among Children In Half

Abstract: Massachusetts' 2006 health reform cut the uninsurance rate for children approximately in half in the first two years following implementation. The state now has the lowest rate of uninsurance among children in the nation. More children became enrolled in MassHealth, the state's Medicaid program, and in employer-sponsored insurance. Most of the coverage increases occurred among lower-income children, many of whom were eligible for but not enrolled in MassHealth prior to reform. We derive a major lesson for nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Hospital discharge data do not collect information on parental smoking or smoke exposure in the home. Second, Massachusetts health care reform has been shown to reduce the number of uninsured children, (Kenney et al, 2010) due to both greater subsidized coverage of children and indirectly through their parents' coverage (Commonwealth of Massachusetts). Although the hospital discharge data includes health insurance status, the census does not collect this information.…”
Section: Tablementioning
confidence: 99%
“…Hospital discharge data do not collect information on parental smoking or smoke exposure in the home. Second, Massachusetts health care reform has been shown to reduce the number of uninsured children, (Kenney et al, 2010) due to both greater subsidized coverage of children and indirectly through their parents' coverage (Commonwealth of Massachusetts). Although the hospital discharge data includes health insurance status, the census does not collect this information.…”
Section: Tablementioning
confidence: 99%
“…We further compared these differences among the 19 to 25 year olds to differences among adolescents aged 12 to 18 in Massachusetts, for whom insurance coverage changed less after health reform. 15 To examine changes in emergency department (ED) visits, we use a similar approach, focusing on the universe of ED visits in Massachusetts and Maryland. We estimated the net effect of opposing influences of insurance coverage on hospital-based behavioral health services against a null hypothesis that service use would not change after coverage expanded.…”
mentioning
confidence: 99%
“…20 It may also be attributable to the fact that this state had not yet implemented simplifications in Medicaid-CHIP enrollment or renewal, which have been shown to reduce instances of uninsurance for children from low-income families. [46][47][48] However, because Massachusetts had high Medicaid-CHIP eligibility levels and rates of insurance prereform, the remaining uninsured CSHCN might be hard-to-reach subjects or undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In the 2 years after initiation of reform, ∼400 000 adults and 35 000 children gained insurance in Massachusetts. [18][19][20] Surveys of physicians in the state reported that, on average, patients had to wait 10 days longer postreform to see a primary care physician. 21 CSHCN who receive care from physicians who see both children and adults (eg, family practitioners) might be particularly likely to experience longer waits in care postreform.…”
mentioning
confidence: 99%